2019
DOI: 10.1016/j.mex.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization method of an indirectly irradiated solar receiver

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…"Maximum allowable Pareto percentage" is set to 70%, and the "Maximum number of iterations" is set to 20. Therefore, the optimization process is terminated when the resulting MOGA edge contains 70 points, which is 70% of the number of samples per iteration of 100, or when the maximum number of iterations is reached [45,46]. In the case of the x−axis part, structural analysis revealed that the maximum stress occurs in the saddle plate, which connects with the other parts.…”
Section: Case Factor 1 Level Factor 2 Levelmentioning
confidence: 99%
“…"Maximum allowable Pareto percentage" is set to 70%, and the "Maximum number of iterations" is set to 20. Therefore, the optimization process is terminated when the resulting MOGA edge contains 70 points, which is 70% of the number of samples per iteration of 100, or when the maximum number of iterations is reached [45,46]. In the case of the x−axis part, structural analysis revealed that the maximum stress occurs in the saddle plate, which connects with the other parts.…”
Section: Case Factor 1 Level Factor 2 Levelmentioning
confidence: 99%
“…The field of energy needs newer methods [1,2] in its battle to sustain its role as the chief driver of economy. In this context, enhanced research is required in the field of renewable energy especially wind energy which is currently the fastest growing source.…”
Section: Introductionmentioning
confidence: 99%